Spondylodiscitis and infectious endocarditis: a round-trip to be considered - Calderaro,Daniela (2008)
The association between spondylodiscitis and endocarditis was first reported in 1965 by de Sèze et al. The most common clinical picture of this association is musculoskeletal symptoms preceding endocarditis diagnosis, but we report here a case of spondylodiscitis complicating endocarditis in its late course. A 70-year-old man, with an established diagnosis of mitral valve endocarditis caused by Streptococcus intermedius, early submitted to surgical treatment because of heart failure, who had an uneventful recovery up to the 12th day of antibiotic therapy when he presented intensive backache, with tenderness in the two lower lumbar vertebras. Spondylodiscitis was confirmed by a magnetic resonance imaging and the treatment was non-esteroidal anti-inflamatory and analgetics drug, with good results, and prolongation of antibiotic treatment up to 3 months. Appropriate diagnosis of this association has important consequences, as the need of a longer antibiotic therapy course, which can range from 6 weeks to 3 months.